Fuel cells to the fore [electric vehicles]. - Gilchrist, T. (IEEE spectrum)
Long regarded as a far-future technology, proton exchange membrane (PEM) hydrogen fuel-cell systems have be more compact and may well finesse the battery problem in electric vehicles. PEM fuel cells operating at about 80°C and employing a thin plastic sheet as their electrolyte, are easy and safe to handle in manufacturing and in later use. Unlike some other electrolytes, their solid plastic membrane can tolerate a modest pressure differential across the cell, making for easy pressurization, which increases power density, simplifies the rest of the system, and reduces cost. A PEM fuel cell is an energy-conversion, not an energy-storage, device. It converts a fuel's chemical energy into electricity directly-that is, electrochemically, with no intermediate thermal or mechanical processes such as occur when a generator is driven by an internal combustion engine. Consequently, the energy conversion is an efficient 50 percent or so, and is clean, its only byproducts being heat and water. The fuel cell will continue to supply electrical power indefinitely, as long as it is supplied with hydrogen and oxygen. The cell itself does not discharge or find its energy depleted, as a battery does. In a car powered by a fuel cell, the storage function is performed by a fuel tank, as in conventional vehicles